Et meningsfullt naturfag for dagens ungdom? - Camilla Schreiner; Svein Sjøberg (Nordina: Nordic Studies in Science Education, 2012)
Can school science become more attractive, interesting and meaningful for young people of today? The point of departure for raising this question is the decline in enrolment in studies in science and technology (S&T) that is apparent in many OECD countries. We draw on perspectives from literature on late modernity and identity construction and we use data from the international comparative project ROSE (the Relevance of Science Education) to shed light on how young people perceive S&Tand some of their criteria for their educational choices. Our focus is on the Nordic situation, but we also provide comparisons with other cultures. We show that young people in all kinds of countries share a positive view on the importance S&T for society and the future development. We note, however, some remarkable differences when it comes to the willingness to engage in S&T-related studies and careers. We use Norwegian data to illustrate the values and concerns that are important for the choice of future jobs for young people. We suggest that there is a mismatch between these values and the values that young people meet in science at school. We argue that science curricula must change to accommodate some of the values of the young generation.